Research Methods in Polemology - Krupa, Marcin (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
The research focuses on a phenomenon with a political, cultural and sociological nature - war. One purpose of my research is to link this phenomenon with the economy. The wider purpose is to raise political science and sociology to a higher level of analysis with the aim of reducing and unifying the social sciences to a stricter level of analysis. This research objective uses the example of war, and enlists mathematical instruments associated not only with the business cycle. Tests are performed on the example of the U.S. business cycle and that country’s military activity. The research shows the reciprocal relationship of these events, the state of the U.S. economy, determined by variations in the parameters of the national income and related to a growing propensity for military activity, which in turn, as the research shows, reduces the number of wars on a global scale. Other aspects of the paper include a description of the history of the research process, the phenomenon of war and issues and problems from the philosophy of science.